2005
DOI: 10.1021/jf051866x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Far-Infrared Irradiation on Catechins and Nitrite Scavenging Activity of Green Tea

Abstract: The processed green tea leaves were irradiated by far-infrared (FIR) at eight temperatures (80, 90, 100, 110, 120, 130, 140, and 150 degrees C) for 10 min. After FIR irradiation, green teas were prepared by soaking the leaves in boiling water, and the physicochemical characteristics of the green tea were determined. FIR irradiation at 90 degrees C increased total phenol contents of green tea from 244.7 to 368.5 mg/g and total flavanol contents from 122.0 to 178.7 mg/g, compared with non-irradiated control. FIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Exposure to excess nitrite from the diet is implicated as a potential etiological factor in the development of stomach and colorectal cancers (Lee et al, 2006). Nitrite reacts with second and third grade amines to form nitrosamine in proteinrich foods, medicines, and residual pesticides.…”
Section: Nitrite Scavenging Activitymentioning
confidence: 99%
“…Exposure to excess nitrite from the diet is implicated as a potential etiological factor in the development of stomach and colorectal cancers (Lee et al, 2006). Nitrite reacts with second and third grade amines to form nitrosamine in proteinrich foods, medicines, and residual pesticides.…”
Section: Nitrite Scavenging Activitymentioning
confidence: 99%
“…TPC of CP extract was determined according to the method of Lee et al (2006). One milliliter of the CP extract was mixed with 1 mL of 2% Na 2 CO 3 , and then centrifuged at 13,400 Â g for 5 min.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…Adding nitrite to sausages forms N-nitrosamines in meat products, thereby, many studies have shown that nitrosamines can be minimized and/or impeded, as nitrite ions are fully scavenged (Rundlöf et al, 2000; Lee et al, 2006). Many intrinsic and/or extrinsic factors enhance nitrite ion development in sausage, indicating that reducing nitrite is a valuable approach to lower N-nitrosamine formation in meat products.…”
Section: Introductionmentioning
confidence: 99%